Autoeficácia docente e escolha pelo ensino superior no contexto do estágio de docência em engenharia - Matos, Mayara da Mota [UNESP] (2015)
This study aims to describe and analyze the relations between the beliefs on self-efficacy and the factors that lead to choose the teaching career in college education in the context of the teaching traineeship in engineering field. In order to find answers for the following questions: How the teaching traineeship influences the engineering graduate students' beliefs of self-efficacy?; Which factors influence the choice of these graduate students for the teaching career? and, Are self-efficacy beliefs related to the choice for college education teaching career? We have delimited as specific objectives: to characterize the student's profile in graduate engineering programs; to measure the level of teacher self-efficacy and the sources of formation of this belief in the context of the teaching traineeship; to identify factors that lead students in these graduate programs to choose being teachers in college education and to correlate the described variables above with the teaching traineeship in Engineering courses. Therefore, we have made use of four search tools, namely: a socio-demographic survey questionnaire, a Teacher Self-efficacy Scale (TES), developed by Polydoro et al. (2004), a Self-efficacy Teachers Sources scale (IAOCHITE; AZZI, 2012) and the free translation into Portuguese and adaptation of Factors Influencing Choice Teaching - FIT - Choice Scale, proposed by Watt, Richardson (2007), who named it as Scale of Factors that influence the choice for teaching. The results indicated that the participants have beliefs of moderate auto-efficacy, with a mean score of 4.46 (SD = 0.69). The average was higher in Intentionality dimension of teaching activities (M = 4.51, SD = 0.70) than in Classroom Management (M = 4.40, SD = 0.72). The sources of information of the most influential Self-efficacy beliefs were, respectively, social persuasion, direct experiences and vicarious experiences, which positively influenced ...